A novel auto-tuning method for fractional order PI/PD controllers. (May 2016) - De Keyser, Robin; Muresan, Cristina I.; Ionescu, Clara M.
Abstract: Fractional order PID controllers benefit from an increasing amount of interest from the research community due to their proven advantages. The classical tuning approach for these controllers is based on specifying a certain gain crossover frequency, a phase margin and a robustness to gain variations. To tune the fractional order controllers, the modulus, phase and phase slope of the process at the imposed gain crossover frequency are required. Usually these values are obtained from a mathematical model of the process, e.g. a transfer function. In the absence of such model, an auto-tuning method that is able to estimate these values is a valuable alternative. Auto-tuning methods are among the least discussed design methods for fractional order PID controllers. This paper proposes a novel approach for the auto-tuning of fractional order controllers. The method is based on a simple experiment that is able to determine the modulus, phase and phase slope of the process required in the computation of the controller parameters. The proposed design technique is simple and efficient in ensuring the robustness of the closed loop system. Several simulation examples are presented, including the control of processes exhibiting integer and fractional order dynamics. Highlights: Novel auto-tuning method for fractional order PI/PD controllers. Process phase slope determined via filtering techniques. The auto-tuning procedure suitable for general processes. A simple and efficient design technique, in the absence of process model.